Respuesta :

ANSWER

The roots are -2,1 and 2

EXPLANATION

The given polynomial function is

[tex]f(x) = 4 {x}^{3} - 4 {x}^{2} - 16x + 16[/tex]

It was given that, (x-2) is a factor of the polynomial.

From the Remainnder Theorem this implies that f(2)=0.

We can rewrite the given polynomial as;

[tex]f(x) = (x - 2)(4 {x}^{2} + 4x - 8)[/tex]

[tex]f(x) = (x - 2)(4 {x}^{2} + 4x - 8)[/tex]

[tex]f(x) = (x - 2)(x + 2)(x - 1)[/tex]

Hence the other roots are:

[tex] (x - 2)(x + 2)(x - 1) = 0[/tex]

[tex]x=2,x=-2,x=1[/tex]
Ver imagen kudzordzifrancis